Zinc Geochemical Cycling in a Phosphorus‐Rich Ocean During the Early Ediacaran. Issue 8 (6th August 2018) - Fan, Haifeng; Wen, Hanjie; Xiao, Chaoyi; Zhou, Ting; Cloquet, Christophe; Zhu, Xiangkun
Abstract: During the early Ediacaran, there was a large influx of phosphorus into the oceans and a resultant high phosphorus concentration in seawater, where multicellular eukaryotes may have been the primary type of marine productivity. The eukaryotes could play a critical role in regulating Zn cycling and isotopes. To establish Zn geochemical cycling patterns in the phosphorus‐rich ocean, this study investigates Zn isotopic signatures of shallow water phosphorite that contains phosphatized microfossils (Weng'an biota) and deep‐water shale from the Doushantuo Formation. Our results indicate that phosphorite commonly preserves heavier Zn isotope composition, with an average of 0.80‰. The positive δ 66 Zn values in phosphorites may be ascribed to Zn isotope fractionation associated with the complexation of Zn with phosphate and the adsorption of isotopically heavy Zn onto Fe‐Mn oxides and organism's surfaces. We argue that phosphorite may represent an important sink of isotopically heavy Zn in a phosphorus‐rich ocean during Earth history. Meanwhile, deep‐water organic‐rich shale shows an enrichment of isotopically light Zn with an average of 0.23‰, which may be attributed to sulfide precipitation in mid‐depth environment. The organic‐rich shale may represent an isotopically light Zn sink. In addition, the highest δ 66 Zn value (0.45‰) in a euxinic black shale may indicate that Zn isotope signal of anoxic deep water is similar to that of modern deep seawater. If that is the case, it suggests that Zn geochemical cycling in the early Ediacaran oceans was similar to that of modern oceans. Key Points: We report Zn isotope compositions of dolostone, phosphorite, and organic‐rich shale from the Doushantuo Formation, South China Phosphorite may represent an important sink of isotopically heavy Zn in a phosphorus‐rich ocean during Earth history Zinc geochemical cycling in the early Ediacaran oceans could be very similar to that of modern oceans